Pendampingan Penyusunan Pedoman Staffing Model Untuk Meningkatkan Efisiensi Usaha Pada PT. Asuransi Bangun Askrida Bandung - Endang Ruchiyat Ruchiyat; Rahmat Rahmat; Dadang Agus Suryanto (Indonesian Community Service and Empowerment Journal (IComSE), 2021)
This community service activity was carried out in Kelurahan, Cijagra, Lengkong District, Bandung City, 40253 with the target of PT. Askrida Insurance Bandung. Based on interviews and observations, the problems faced by partners today are the amount of premium rates that are difficult to compete with similar companies, poor work governance that requires employees to work overtime every day and the slow delivery of services to customers. This program has the following objectives: 1) improving the welfare of the community through the improvement of healthy financial institutions, especially insurance 2) improving the skills and professionalism of the community 3) increasing business efficiency for partners so that they are able to compete and serve the community better. This activity uses two approaches, namely the training and mentoring approach. The training approach includes: 1) job analysis training; 2) training on work load analysis (work load analysis); and 3) skills training for the preparation of staffing model guidelines. While the mentoring methods include: 1) assistance in conducting job analysis; 2) workload analysis assistance; 3) assistance in the preparation of staffing model guidelines. The results of this community service activity have an impact on clients to be able to organize their employees well, so as to improve business efficiency and serve the community better.